Errors of Upright Perception in Patients With Vestibular Migraine - Winnick, Ariel; Sadeghpour, Shirin; Otero-Millan, Jorge; Chang, Tzu-Pu; Kheradmand, Amir (Frontiers in Neurology, 2018)
Patients with vestibular migraine (VM) often report dizziness with changes in the head or body position. Such symptoms raise the possibility of dysfunction in neural mechanisms underlying spatial orientation in these patients. Here we addressed this issue by investigating the effects of static head tilt on errors of perception of upright in a group of 27 VM patients in comparison with a group of 27 healthy controls. Perception of upright was measured in a dark room using a subjective visual vertical (SVV) paradigm at three head tilt positions (upright, +/- 20º). VM patients were also surveyed about the quality of their dizziness and spatial symptoms during daily activities. In upright head position, SVV errors was within the normal ranges for VM patients and healthy controls (two degrees from true vertical). During the static head tilts of 20º to the right, VM patients showed larger SVV errors consistent with overestimation of the tilt magnitude (i.e. as if they felt further tilted towards the right side) (VM: -3.21° ± 0.93 vs. Control: 0.52° ± 0.70; p=0.002). During the head tilt to the left, SVV errors in VM patients did not differ significantly from controls (VM:0.77° ± 1.05 vs. Control: -0.04° ± 0.68; p=0.52). There was no significant difference in SVV precision between the VM patients and healthy controls at any head tilt position. Consistent with the direction of the SVV errors in VM patients, they largely reported spatial symptoms toward the right side. These findings suggest an abnormal sensory integration for upright perception in vestibular migraine, related to daily dizziness in these patients.